Pendidikan Agama Kristen sebagai Instrumen Pencegahan Phubbing pada Remaja - Tambunan, Ruhut Parningotan; Arifianto, Yonatan Alex (GRAFTA: Journal of Christian Religion Education and Biblical Studies, 2026)
The rapid development of digital technology in the 21st century has presented both opportunities and challenges for young people. Social media and mobile devices have become an integral part of their daily lives, but on the other hand, they have the potential to degrade the quality of face-to-face interactions. Education in the digital age needs to respond to these changes with relevant strategies so that the character building of young people is not neglected. The phenomenon of phubbing, which is the behaviour of ignoring others in direct interaction because of a greater focus on mobile phones, has an impact on the mental health, social relationships, and spirituality of adolescents. The purpose of this study is to examine the role of Christian Religious Education as an instrument for preventing phubbing behaviour through the instilling of values of love, empathy, and digital ethical awareness. The research method used a descriptive-analytical approach, concluding that phubbing is a behaviour of ignoring social interaction due to focus on digital devices, which can be prevented through the application of moral education. Moral education is an important foundation in shaping adolescents' awareness to avoid the negative impacts of phubbing on mental and spiritual health. In addition, Christian Religious Education teachers play a strategic role in instilling digital ethics, so that awareness and control of phubbing behaviour can be achieved. The novelty of this research lies in the integration of the concept of digital ethics with theological values in Christian Religious Education as a preventive approach to phubbing behaviour, which not only emphasises general morality but also the formation of spiritual and relational awareness in the use of digital technology. Abstrak Perkembangan teknologi digital yang sangat pesat pada abad ke-21 telah menghadirkan peluang sekaligus tantangan bagi kehidupan remaja. Media sosial dan perangkat gawai menjadi bagian yang tidak terpisahkan dari keseharian mereka, namun di sisi lain memunculkan potensi degradasi kualitas interaksi tatap muka. Pendidikan di era digital perlu merespons perubahan ini dengan strategi yang relevan agar pembentukan karakter remaja tidak terabaikan. Fenomena  phubbing sebagai perilaku mengabaikan orang lain dalam interaksi langsung karena lebih fokus pada ponsel, yang berdampak pada kesehatan mental dan relasi sosial serta spiritualitas remaja. Tujuan penelitian ini adalah untuk mengkaji peran Pendidikan Agama Kristen sebagai instrumen pencegahan perilaku phubbing melalui penanaman nilai-nilai kasih, empati, dan kesadaran etis digital. Metode penelitian menggunakan pendekatan deskriptif-analitis maka dapat disimpulkan bahwa phubbing merupakan perilaku mengabaikan interaksi sosial akibat fokus pada perangkat digital yang dapat dicegah melalui penerapan pendidikan moral. Pendidikan moral menjadi dasar penting dalam membentuk kesadaran remaja agar terhindar dari dampak negatif phubbing terhadap kesehatan mental dan spiritual. Selain itu, guru Pendidikan Agama Kristen memegang peran strategis dalam menanamkan etika digital, sehingga kesadaran dan pengendalian perilaku phubbing dapat tercapai. Kebaruan penelitian ini terletak pada integrasi konsep etika digital dengan nilai-nilai teologis dalam Pendidikan Agama Kristen sebagai pendekatan preventif terhadap perilaku phubbing, yang tidak hanya menekankan aspek moralitas umum tetapi juga pembentukan kesadaran spiritual dan relasional dalam penggunaan teknologi digital.